The Use of Infrapatellar Fat Pad-Derived Mesenchymal Stem Cells in Articular Cartilage Regeneration: A Review - ÇALIKOĞLU KOYUNCU, AYŞE CEREN (MDPI, 2021)
Cartilage is frequently damaged with a limited capacity for repair. Current treatment strategies are insufficient as they form fibrocartilage as opposed to hyaline cartilage, and do not prevent the progression of degenerative changes. There is increasing interest in the use of autologous mesenchymal stem cells (MSC) for tissue regeneration. MSCs that are used to treat articular cartilage defects must not only present a robust cartilaginous production capacity, but they also must not cause morbidity at the harvest site. In addition, they should be easy to isolate from the tissue and expand in culture without terminal differentiation. The source of MSCs is one of the most important factors that may affect treatment. The infrapatellar fat pad (IPFP) acts as an important reservoir for MSC and is located in the anterior compartment of the knee joint in the extra-synovial area. The IPFP is a rich source of MSCs, and in this review, we discuss studies that demonstrate that these cells have shown many advantages over other tissues in terms of ease of isolation, expansion, and chondrogenic differentiation. Future studies in articular cartilage repair strategies and suitable extraction as well as cell culture methods will extend the therapeutical application of IPFP-derived MSCs into additional orthopedic fields, such as osteoarthritis. This review provides the latest research concerning the use of IPFP-derived MSCs in the treatment of articular cartilage damage, providing critical information for the field to grow.
Keywords: infrapatellar fat pad; mesenchymal stem cells; adipose tissue; osteoarthritis; articular cartilage; ADIPOSE-TISSUE; STROMAL CELLS; PROGENITOR CELLS; BONE-MARROW; KNEE; DIFFERENTIATION; OSTEOARTHRITIS; DEFECTS; INFLAMMATION; SYNOVIUM